Psychometric Validation of the PERMA-Profiler as a Well-Being Measure for Young Adult Survivors of Pediatric Central Nervous System Tumor. (July 2022) - Grenawalt, Teresa Ann; Umucu, Emre; Reyes, Antonio; Baylin, Andrea; Strauser, David R.; Tansey, Timothy N.; Wagner, Stacia
This study aims to validate a measure of well-being, the PERMA-Profiler, among a sample of young adult survivors of pediatric central nervous system (CNS) tumor. Measurement structure of the PERMA-Profiler was evaluated using exploratory factor analysis and confirmatory factor analysis using pretest–posttest data. Reliability and concurrent validity of the PERMA-Profiler were examined. This study included 127 young adult survivors of pediatric CNS tumor between the ages of 18 and 30 ( M = 23.83, SD = 3.00) years. The results of factor analyses yielded a single-factor solution for well-being. Significant relationships between well-being and happiness, life satisfaction, perceived stress, and physical health were observed, providing support for the concurrent validity of the PERMA-Profiler. The PERMA-Profiler displayed good internal consistency and test–retest reliability. The PERMA-Profiler can help rehabilitation researchers and counselors better evaluate well-being in young adult survivors of pediatric CNS tumor, which provides opportunity for more targeted psychosocial interventions.